Rancang Bangun, Implementasi Dan Persepsi Petani Milenial Terhadap Aplikasi Analisa Usaha Tani Berbasis Android Di Kabupaten Tulungagung - Oktaviyanti, Milla; Sumarji, Sumarji; Suparno, Suparno (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
The age of Indonesian farmers is dominated by old age and the education of farmers is only dominated by elementary school graduates. This makes it difficult to transfer knowledge and technology, so the desire of today's children to enter the world of agriculture is needed. Millennial farmers are farmers aged between 19 to 39 years. The existence of millennial farmers increases innovation in society, especially productive entrepreneurs regardless of age. To find out the benefits and whether or not the business run by millennial farmers is feasible, it is necessary to calculate the Farm Business Analysis. The purpose of this research is to describe the farm analysis system then design an android-based farm analysis application, implement the farm analysis application and how the perception of the farm analysis application for millennial farmers in Tulungagung Regency. The method used in this research is the Waterfall method, where there are 5 stages. After making the application, the application will be used by millennial farmers and the perception of the usefulness and convenience of the application will be measured through the questionnaire distributed. From the results of the research obtained, namely the farm calculator application (KalkuTani) can be accepted by millennial farmers and applied to their farms.